Childhood, human rights and citizenship - Díaz Arce, Sergio Ruiz (2020)
Although the legal scenario for children after the advent of the International Convention on the Rights of the Child has generated an impact on national laws, the exercise of these rights by their holders continues to present some restrictions.  In this sense, the present article aims to perform an analysis on the paradigm shift in childhood as associated to the notion of citizenship, which is understood as a process of affirmation and conquest of rights.  Thence, the analysis initiates from an old conception of protection that considered the minor as an incapable and incomplete being, in contrast to a new protection paradigm, resulting from new laws for children and their condition as holders of rights.  In this context, childhood citizenship is understood as opposed to the idea of ​​ “future citizens”, based on the rights that were acquired, including the right to participate and be social actors, in accordance with the development of progressive autonomy.  Therefore, it is considered necessary to affirm the citizenship of children through the principle of progressive autonomy in order to achieve equal rights among people and build more democratic societies.